IMPLEMENTASI KEBIJAKAN LARANGAN PEMBUKAAN LAHAN PERTANIAN DENGAN CARA DIBAKAR BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 DI DESA WARUKIN KECAMATAN TANTA KABUPATEN TABALONG - Rahmi Hayati (stiatabalong.ac.id, 2018)
This study aims to analyze the Implementation of the Policy on the Ban on the Opening of Agricultural Land by Burning Based on Law Number 32 of 2009 in Warukin Village, Tanta Subdistrict, Tabalong Regency and to find out what costs affect the Implementation of the Banned Agricultural Land Prohibition Policy - Law Number 32 of 2009 in Warukin Village, Tanta Subdistrict, Tabalong Regency. Data Collection Techniques in this study is observation and interview. The data collected was then described and analyzed with descriptive analysis techniques that provided an overview of the Implementation of the Policy on the Ban on the Opening of Agricultural Land by Burning Based on Law Number 32 of 2009 in Warukin Village, Tanta Subdistrict, Tabalong Regency with three stages: data reduction, data presentation and reduction of conclusions. The results of the study are as follows: 1) Policy for Prohibiting the Opening of Agricultural Land by Burning Based on Law Number 32 of 2009 in Warukin Village, Tanta Subdistrict, Tabalong District, in fact the field has been implemented; 2) It turns out that the fact that Bambang Sunggono is a factor that is an obstacle or an obstacle to policy implementation is not fully proven in the field. But other than that there were other obstacles such as human resources and lack of facilities and infrastructure and funds. Keywords: implementation; policy; law number 32 of 2009